Sweet biochemistry remembering structures, cycles, and pathways by mnemonics - Asha Kumari (Elsevier, Academic Press, 2018)
Sweet Biochemistry: Remembering Structures, Cycles, and Pathways by Mnemonics makes biochemistry lively, interesting and memorable. by connecting objects, images and stories. Dr. Kumari has converted cycles and difficult pathways into very simple formula, very short stories and images which will help readers see familiar things in complicated cycles and better visualize biochemistry.--Provided by publisher.